Distributed Differential Space-Time Spreading for the Asynchronous Relay Aided Interference-Free Cooperative CDMA Uplink - Sugiura, S; Chen, S; Hanzo, L (2010 IEEE International Conference on Communications, 2010)
In this paper, we propose a differential Space-Time Coding (STC) scheme designed for asynchronous cooperative networks, where neither channel estimation nor symbol-level synchronization is required at the cooperating nodes. More specifically, our system employs differential encoding during the broadcast phase and a Space-Time Spreading (STS)-based amplify-and-forward scheme during the cooperative phase in conjunction with interference rejection Direct Sequence (DS) spreading codes, namely Loosely Synchronized (LS) codes. The LS codes exhibit a so-called Interference Free Window (IFW), where both the autocorrelation and cross-correlation values of the codes become zero. The IFW allows us to eliminate both the Multi-User Interference (MUI) as well as the potential dispersion-induced orthogonality degradation of the cooperative space-time codeword and the interference imposed by the asynchronous transmissions of the relay nodes. Furthermore, the destination node can beneficially combine both the directly transmitted and the relayed symbols using low-complexity correlation operations combined with a hard-decision detector. Our simulation results demonstrate that the proposed Cooperative Differential STS (CDSTS) scheme is capable of combating the effects of asynchronous uplink transmissions without any Channel State Information (CSI), provided that the maximum synchronization delay of the relay nodes is within the width of IFW. It will be demonstrated that in the frequency-selective environment considered our CDSTS arrangement is capable of exploiting both space-time diversity and multi-path diversity with the aid of a RAKE combiner.